2011
DOI: 10.1007/s00330-011-2196-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of primary lesion FDG uptake for choice between oesophagectomy and endoscopic submucosal dissection for resectable oesophageal squamous cell carcinomas

Abstract: Primary lesion FDG visibility can be one of the indicators for choosing between oesophagectomy and ESD for resectable oesophageal SCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
(93 reference statements)
1
6
0
Order By: Relevance
“…Some previous studies showed low sensitivity of FDG-PET for superficial ECs. The results of our study are consistent with these, and our study is highly important because it confirms the low sensitivity of FDG-PET for ECs in the screening setting[11,13,14,18]. Because of the very low sensitivity, it is believed that FDG-PET is difficult to use as a screening modality for ECs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some previous studies showed low sensitivity of FDG-PET for superficial ECs. The results of our study are consistent with these, and our study is highly important because it confirms the low sensitivity of FDG-PET for ECs in the screening setting[11,13,14,18]. Because of the very low sensitivity, it is believed that FDG-PET is difficult to use as a screening modality for ECs.…”
Section: Discussionsupporting
confidence: 89%
“…Although the usefulness of FDG-PET for the assessment of EC extension and metastasis, detection of EC recurrence after treatment, and evaluation of the response to therapy for EC has been well examined[11-17], only limited data are available on the performance of FDG-PET for EC screening. With respect to the diagnostic ability of FDG-PET for primary EC lesions, EC that invades the submucosal layer or deeper can reportedly be detected, but more superficial ECs are difficult to detect[11,13,14,18]. Based on this finding, it can be hypothesized that FDG-PET is not suitable for EC screening.…”
Section: Introductionmentioning
confidence: 99%
“…Westeterp et al [21] have revealed that tumor size and GLUT-1 expression had an influence on SUV max in ESCC. In contrast, Nakajo et al [22] have suggested that 18 F-FDG uptake in ESCC is associated with p-tumor size, GLUT-1 expression, and tumor depth. However, the p-tumor size is estimated on the basis of the largest diameter and does not always reflect accurate tumor cell density.…”
Section: Discussionmentioning
confidence: 88%
“…The rate of glucose transport via GLUT-1 may be altered under conditions in which the metabolic rate must be adjusted, including during cell division (mitosis and meiosis), differentiation, transformation and nutrient starvation (4). In previous studies (5)(6)(7)(8)(9)(10)(11), Glut-1 expression has been correlated with lymph node metastasis, poor survival rate and clinical stage of head and neck carcinoma (HNC).…”
Section: Introductionmentioning
confidence: 99%